Tailor-made sRNAs - Apura, Patrícia (2020)
Pseudomonas putida is a highly attractive production system for industrial needs. However, for its improvement as a biocatalyst at the industrial level, modulation of its gene expression is urgently needed. We report the construction of a plasmid expressing a small RNA-based system with the potential to be used for different purposes. Due to the small RNAs modular composition, the design facilities and ability to tune gene expression, they constitute a powerful tool in genetic and metabolic engineering. In the tool presented here, customized sRNAs are expressed from a plasmid and specifically directed to any region of a chosen target. Expression of these customized sRNAs is shown to differentially modulate the level of endogenous and heterologous reporter genes. The antisense interaction of the sRNA with the mRNA produces different outcomes. Depending on the particularity of each sRNA-target mRNA pair, we demonstrate the duality of this system, which is able either to decrease or increase the expression of the same given gene. This system combines high specificity with the potential to be widely applied, due to its predicted ability to modulate the expression of virtually any given gene. This plasmid can be used to redesign P. putida metabolism, fulfilling an important industrial gap.